2013
DOI: 10.1371/journal.pone.0056476
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Separation and Antibiotics Selection Enable Enrichment of Cells with ZFN/TALEN-Induced Mutations

Abstract: The ability to enrich cells with targeted mutations greatly facilitates the process of using engineered nucleases, including zinc-finger nucleases and transcription activator-like effector nucleases, to construct such cells. We previously used surrogate reporters to enrich cells containing nuclease-induced mutations via flow cytometry. This method is, however, limited by the availability of flow cytometers. Furthermore, sorted cells occasionally fail to form colonies after exposure to a strong laser and hydros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 27 publications
4
61
0
Order By: Relevance
“…Consistent with this, we always detect mutations by T7E1 assays in mutated cells, whereas previous descriptions of episomal reporters often could not detect mutations in unselected cells (41,43,46). In such instances where the mutation load in unselected cells is undetectable by T7E1 assay (41,43,46), the -fold changes were calculated to be quite high, based on a denominator that is estimated (i.e. a mutation frequency of 0.5-1%).…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with this, we always detect mutations by T7E1 assays in mutated cells, whereas previous descriptions of episomal reporters often could not detect mutations in unselected cells (41,43,46). In such instances where the mutation load in unselected cells is undetectable by T7E1 assay (41,43,46), the -fold changes were calculated to be quite high, based on a denominator that is estimated (i.e. a mutation frequency of 0.5-1%).…”
Section: Discussionsupporting
confidence: 83%
“…To compare the activities of programmable nucleases expressed by minicircles versus conventional plasmids, we used pcDNA 3.0 ( Figure 1a) instead of the minicircle parental plasmid (Figure 1b) as the control vector because pcDNA 3.0 has been the primary vector used for programmable nuclease expression; [50][51][52] furthermore, the minicircle parental plasmid has not been used as an expression vector for programmable nucleases. Electrophoresis of the isolated minicircle vector showed that a major band of minicircle and a minor band of parental plasmid was present (Figure 1c).…”
Section: Preparation Of Minicircle Dna Encoding Zfns or Talensmentioning
confidence: 99%
“…[51][52][53][54][55][56] The reporter consists of the mRFP gene, followed by the nuclease's target sequence and the enhanced green fluorescent protein (eGFP) gene, which is out of frame with the mRFP gene ( Figure 2a). If ZFNs or TALENs make a double-strand break at the target sequence of the reporter, frame shifts occur because of the generation of indels in the target sequence through the error-prone non-homologous-end-joining repair process, resulting in functional eGFP expression.…”
Section: Preparation Of Minicircle Dna Encoding Zfns or Talensmentioning
confidence: 99%
See 2 more Smart Citations